Behavioral genetics of the mouse. Volume 2, Genetic mouse models of neurobehavioral disorders - Pietropaolo, Susanna; Sluyter, Frans; Crusio, W. E.; Cambridge eBooks (Cambridge : Cambridge University Press, 2014)
The second volume of Behavioral Genetics of the Mouse provides a comprehensive overview of the major genetically modified mouse lines used to model human neurobehavioral disorders; from disorders of perception, of autonomous and motor functions to social and cognitive syndromes, drug abuse and dependence as well as neurodegenerative pathologies. Mouse models obtained with different types of genetic manipulations (i.e. transgenic, knockout/in mice) are described in their pathological phenotypes, with a special emphasis on behavioral abnormalities. The major results obtained with many of the existing models are discussed in depth highlighting their strengths and limitations. A lasting reference, the thorough reviews offer an easy entrance into the extensive literature in this field, and will prove invaluable to students and specialists alike.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Mice -- Genetics; Behavior genetics; Electronic books